Management of shrunken cheeks by hollow buccal cheek plumper prosthesis - Parthasarathy Natarajan; Seenivasan Madhan Kumar; Shanmuganathan Natarajan; Fathima Banu Raza (Wolters Kluwer Medknow Publications, 2021)
Aging and a long period of edentulousness causes resorption of the maxillary residual ridge, resulting in narrowing of the arch and loss of facial muscle support that leads to the sunken appearance of cheeks. In completely edentulous patients, though the conventional complete denture does offer provision to the muscles encircling the mouth, yet the cheek plumber prosthesis is required to improve the muscle tone. This case report highlights the advantages and the sequential steps required in the indigenous method of fabricating a hollow cheek plumper appliance for a completely edentulous patient with a sunken appearance.